A Translation Analysis Of Adjective Phrase In I Am Number Four Novel By Pittacus Lore And Its Translation - Saifurrakhim, Fakikh; , Dra. Dwi Harjanti, M.Hum; , Dr. Anam Sutopo, M.Hum (2013)
This study focuses on analyzing the shift of adjective phrase translation using the theory of translation shift by Catford. This study aims at 1) classifying the translation shift of adjective phrase found in "I Am Number Four" and its translation, 2) describing the equivalence and non equivalence of the adjective phrase translation found in "I Am Number Four" and its translation. This research applies descriptive qualitative method. The data is a novel by Pittacus Lore entitled "I Am Number Four". The way to collect data is using docummentation method. The analyzed data are adjective phrase found in the novel "I Am Number Four". The results show that there are 103 data or 98,10% belong to level shift and 2 data or 1,90% belong to structure shift. There are 6 classification of adjective phrase translation 1) adjective phrase is translated into adjective, 2) adjective phrase is translated into verb, 3) adjective phrase is translated into adverb phrase, 4) adjective phrase is translated into verb phrase, 5) adjetcive phrase is translated into clause, and 6) adjective phrase is omitted. On the equivalent of translation, there are 103 data or 98,10% data belong to equilvalent translation and 2 data or 1,90% data belong to non equivalent translation, so the research assume that the translation of adjective phrase in "I Am Number Four" novel is good.